2022
DOI: 10.1108/lhs-02-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Leading in a time of crisis: exploring early experiences of health facility leaders during the COVID-19 pandemic in Nigeria’s epicentre

Abstract: Purpose The COVID-19 pandemic has had a disruptive effect on the health system. Health facility leaders were at the forefront of maintaining service delivery and were exposed to varied stressors in the early phase of the pandemic. This study aims to explore the leadership experiences of health facility leaders during the early phase of the COVID-19 pandemic in Nigeria’s epicentre. Design/methodology/approach This study conducted an exploratory descriptive qualitative study. To achieve this, 33 health facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Had it not been for external concerns such as distance, transport, the poor reception of certain staff, or even complications during treatment, the pandemic did not have a considerable impact according to MNHS users. The above problems mentioned by MNHS users in our study are similar to those revealed by Balogun et al ( 2021) [23] when they confirmed that 18.13% of women were unable to access services because they did not have means of transport.…”
Section: Mnhs User Needs Metsupporting
confidence: 91%
“…Had it not been for external concerns such as distance, transport, the poor reception of certain staff, or even complications during treatment, the pandemic did not have a considerable impact according to MNHS users. The above problems mentioned by MNHS users in our study are similar to those revealed by Balogun et al ( 2021) [23] when they confirmed that 18.13% of women were unable to access services because they did not have means of transport.…”
Section: Mnhs User Needs Metsupporting
confidence: 91%
“…Strong, adaptive leadership at all levels of health care systems was needed to effectively address the immense crisis at hand. 36,37 Findings from this pilot QI initiative suggest that MCDs faced many new challenges, requiring them to perform unfamiliar tasks and manage numerous overlapping challenges (eg, staffing shortages and reassignments, safety concerns, changes to patient appointments, backlogs in essential services), all while also trying to continue with the journey to high reliability. Despite the challenges leaders faced, they recognized the need to manage competing priorities early and effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research highlights how leaders had to modify their day-to-day responsibilities because of the wide disruptions caused by the COVID-19 pandemic, even when not on the journey to becoming an HRO. 36,37 Some participants felt compelled to stay committed to the HRO journey despite numerous competing demands. They stayed committed to looking for opportunities to progress by implementing HRO principles and practices to achieve safety, quality, and efficiency goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation